Christocentric Exemplarism and the Imitation of Jesus - Pope, Stephen J. (New blackfriars, 2020)
This article examines the version of Christocentric exemplarism recently proposed by theologian Patrick Clark, whose Thomistic virtue ethics incorporates features of Linda Zagzebski's exemplarist moral theory. This article suggests that Clark and similar approaches to Christocentric virtue ethics would be better situated to appropriate Zagzebski's insights into exemplarity if it gave more prominence to the imitation of Jesus.